Polyphonic poetics of Anatoly Kim's works: semantics and functions - Baizhigit , B.S.; Safronova, L.V.; Kanafina, M.A. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
The purpose of this article is to investigate the phenomenon of polyphony in A. Kim's prose, which manifests at various levels of its poetics, primarily in speech perversions. The plot core of the novel Joys of Paradise, the main object of analysis in this article, is rooted in Indian philosophical and religious traditions of the transmigration of the soul, "samsara". In the final transmigration, where the soul is meant to achieve perfection, the protagonist's "soul" receives a vessel in which it attains its goal and will no longer wander the world in search of the Joys of Paradise. The attainment of this harmony is marked in A. Kim's novel by the renunciation of the disharmony in the author-hero's speech sphere, and the removal of the leitmotivic speech schism. Schism, absurdist tendencies in the speech and imagery of A. Kim's works Squirrel and Settlement of Centaurs are conditioned by the polyphony of voices, character transformations, the "quartering" of the hero's personalities, animism, various types of neologisms, a wide associative array of metaphorical expressions, and synonymous lexical and syntactic constructions that unite incompatible elements.